Project Contingent Repudiation Risk in the Model of North-South Lending - GURDGIEV, CONSTANTIN (My University, 2004)
The present model proposes an extension of the Gertler and Rogoff (1990) model of international lending in the presence of moral hazard and the possibility of state-contingent and project-dependent repudiation risk along the lines of Lane (1999). By linking the level of repudiation risk to the size of the project, we show that investment projects arising in the marketplace will be constrained in the size of capital by the repudiation risk, even in case of the repudiation risk applying to the bad state of nature alone. This amplifies the results shown in Lane (1999) and can be interpreted as a debt ceiling within the context of international lending. The model provides a natural connection between the exogenous monitoring institutions development, the degree of corruption and bankruptcy/limited liability laws to the ability of entrepreneurs to raise investment funding.
PUBLISHED
Keywords: Economics; Moral Hazard; Investment; Repudiation Risk; State Contingency